![\: the \: value \: of \: n = ?if5+8+11....+10terms3+5+7+....+nterms=7.thenthevalueofn=?\ \textless \ br /\ \textgreater \ \ \textless \ br /\ \textgreater \ 2. \sf \: if \: \: \: \dfrac{ a + bx}{a - bx} = \dfrac{b + cx}{b - cx} = \dfrac{c + dx}{c - dx} \: .then \: a , b , c , d \: are \: inifa−bxa+bx=b−cxb+cx=c−dxc+dx.thena,b,c,darein \: the \: value \: of \: n = ?if5+8+11....+10terms3+5+7+....+nterms=7.thenthevalueofn=?\ \textless \ br /\ \textgreater \ \ \textless \ br /\ \textgreater \ 2. \sf \: if \: \: \: \dfrac{ a + bx}{a - bx} = \dfrac{b + cx}{b - cx} = \dfrac{c + dx}{c - dx} \: .then \: a , b , c , d \: are \: inifa−bxa+bx=b−cxb+cx=c−dxc+dx.thena,b,c,darein](https://tex.z-dn.net/?f=%5C%3A+the+%5C%3A+value+%5C%3A+of+%5C%3A+n+%3D+%3Fif5%2B8%2B11....%2B10terms3%2B5%2B7%2B....%2Bnterms%E2%80%8B%3D7.thenthevalueofn%3D%3F%5C++%5Ctextless+%5C+br+%2F%5C++%5Ctextgreater+%5C+%5C++%5Ctextless+%5C+br+%2F%5C++%5Ctextgreater+%5C+2.%C2%A0%5Csf+%5C%3A+if+%5C%3A+%5C%3A+%5C%3A+%5Cdfrac%7B+a+%2B+bx%7D%7Ba+-+bx%7D+%3D+%5Cdfrac%7Bb+%2B+cx%7D%7Bb+-+cx%7D+%3D+%5Cdfrac%7Bc+%2B+dx%7D%7Bc+-+dx%7D+%5C%3A+.then+%5C%3A+a+%2C+b+%2C+c+%2C+d+%5C%3A+are+%5C%3A+inifa%E2%88%92bxa%2Bbx%E2%80%8B%3Db%E2%88%92cxb%2Bcx%E2%80%8B%3Dc%E2%88%92dxc%2Bdx%E2%80%8B.thena%2Cb%2Cc%2Cdarein)
Note:-
1. Irrelevant answers will be reported.
2. Answer will detailed explanation.
Answers
We have to find the value of 'n' in the given expression:
\frac{3+5+7+....+n}{5+8+11+...+10 terms}=7
5+8+11+...+10terms
3+5+7+....+n
=7
since the series given in numerator and denominator is in arithmetic progression as the common difference is same throughout both the series.
Sum of Arithmetic Progression = \frac{n}{2}[2a+(n-1)d)]
2
n
[2a+(n−1)d)]
So, \frac{\frac{n}{2}[(2 \times 3)+(n-1)2)]}{\frac{10}{2}(2(5)+(9 \times 3))}= 7
2
10
(2(5)+(9×3))
2
n
[(2×3)+(n−1)2)]
=7
\frac{\frac{n}{2}[(6)+(n-1)2)]}{\frac{10}{2}(10+27)}= 7
2
10
(10+27)
2
n
[(6)+(n−1)2)]
=7
\frac{n(6+2n-2)}{2}= 7 \times 5 \times 37
2
n(6+2n−2)
=7×5×37
\frac{n(4+2n)}{2}= 7 \times 5 \times 37 \times 2
2
n(4+2n)
=7×5×37×2
4n+2n^{2}-2590=04n+2n
2
−2590=0
2n+n^{2}-1295=02n+n
2
−1295=0
n^{2}+2n-1295=0n
2
+2n−1295=0
n^{2}+37n-35n-1295=0n
2
+37n−35n−1295=0
n(n+37)-35(n+37)=0n(n+37)−35(n+37)=0
(n-35)(n+37)=0(n−35)(n+37)=0
Since 'n' can'not be negative.
So, n=35.
So, the value of 'n' in the given expression is 35.